Why Did the New Testament Writers Appeal to the Old Testament?. (September 2015) - Evans, Craig A.
Jesus' use of the Old Testament was innovative and experiential. Although his use of scripture was foundational for the theology of the early church, early Christian teachers and writers were not limited by it. Some of the New Testament writers appealed to certain passages because Jesus appealed to them and they had become part of the 'biblical theology' of the Jesus movement in the post-Easter setting. Other texts were appealed to because they clariﬁed new problems and questions that the early church faced as it grew and expanded into lands outside of Israel.